Time control, catecholamines and back pain among young nurses - Elfering, Achim; Grebner, Simone; Semmer, Norbert K.; Gerber, Hans (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study had two objectives. First, it addressed concern with the contribution of work stressors and resources to the development of back pain, over and above the influence of biomechanical work factors. Second, using recent models about the role of the sympathetic-adrenal medullar system in musculoskeletal problems as its basis, it tested whether low-back pain is associated with higher levels of catecholamines. ' ' METHODS ': 'Altogether 114 nurses filled out a questionnaire in their first year of practice and again one year later. In addition, in a subsample of 24 nurses studied intensively at follow-up, urinary catecholamines were assessed at noon, before the end of work, in the evening, and at corresponding times on a day off. Daily stressful experiences and daily mood were also recorded. ' ' RESULTS ': 'With control for baseline pain, biomechanical workload, and other potentially confounding variables, time control at the beginning of the study predicted low-back pain a year later. In the subsample, the epinephrine and norepinephrine levels were higher in those reporting more frequent episodes of back pain, the largest differences occurring before the end of the workday. In addition, control over stressful events at work was lower in this group. ' ' CONCLUSIONS ': 'Time control is a risk factor for low-back pain among nurses beyond the influence of physical work load. Low control at work may increase the activity of the sympathetic-adrenal medullar system, which seems to play an important role in the development of musculoskeletal pain.
Keywords: back pain; catecholamines; job beginner; nurse; stressful event; time control